2011
DOI: 10.1016/j.watres.2011.08.035
|View full text |Cite
|
Sign up to set email alerts
|

The rheological behaviour of anaerobic digested sludge

Abstract: Producing biogas energy from the anaerobic digestion of wastewater sludge is one of the most challenging tasks facing engineers, because they are dealing with vast quantities of fundamentally scientifically poorly understood and unpredictable materials; while digesters need constant flow properties to operate efficiently. An accurate estimate of sludge rheological properties is required for the design and efficient operation of digestion, including mixing and pumping. In this paper, we have determined the rheo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 18 publications
5
85
0
1
Order By: Relevance
“…The viscosity of the reactor sludge in the control reactor (R2) ranged between 2.0 ± 0.2 and 7.7 ± 0.3 mPa*s throughout the experiment (Fig. 1h), which was in the same range as previously reported values for reactor liquids of processes digesting sewage sludge (Baudez et al 2011(Baudez et al , 2013. It should also be noted that in addition to TS, changes in parameters such as, e.g., particle size, polymeric substances, and ion concentrations, may have contributed to changes in viscosity of the R1 upon codigestion of OFMSW as an additional substrate (Nges et al 2012;Moestedt et al 2016;Lindorfer and Demmig 2016).…”
Section: Resultssupporting
confidence: 84%
“…The viscosity of the reactor sludge in the control reactor (R2) ranged between 2.0 ± 0.2 and 7.7 ± 0.3 mPa*s throughout the experiment (Fig. 1h), which was in the same range as previously reported values for reactor liquids of processes digesting sewage sludge (Baudez et al 2011(Baudez et al , 2013. It should also be noted that in addition to TS, changes in parameters such as, e.g., particle size, polymeric substances, and ion concentrations, may have contributed to changes in viscosity of the R1 upon codigestion of OFMSW as an additional substrate (Nges et al 2012;Moestedt et al 2016;Lindorfer and Demmig 2016).…”
Section: Resultssupporting
confidence: 84%
“…Several factors that potentially influence N losses by NH 3 volatilization during and after field spreading are affected by anaerobic digestion: Reduction of dry matter content (e.g., Asmus et al 1988) and viscosity Baudez et al 2011) can increase the infiltration of liquid manure into the soil, thereby decreasing the exchange surface of slurry with the atmosphere thus lowering NH 3 volatilization (Rubaek et al 1996;Sommer and Hutchings 2001). However, digestion leads simultaneously to an increase in manure pH (by 0.5-2.0 U) and of the ammonium concentration (relative increase of >20 %) (Möller and Müller 2012); both factors promote N losses via NH 3 volatilization (e.g., Gericke et al 2012;Ni et al 2012;Sommer and Hutchings 2001 In concordance with the described potential effects, contradictory results regarding the effects of anaerobic digestion on NH 3 volatilization after field application of digestates have been reported in literature: Some researchers report a decrease of NH 3 losses after soil application of digested animal manures, others report an increase of losses, and others did not found any or ambiguous effects (Table 3).…”
Section: Impact Of Anaerobic Digestion On Ammonia Volatilization Frommentioning
confidence: 99%
“…Monteiro (1997) showed that anaerobic digested sludge rheology can be described using the Herschel-Bulkley model, for which the rheological characteristics decreased with the degree of fermentation. More recently, Baudez et al (2011a) highlighted a more complex behaviour with shear banding at low shear rates and a viscosity plateau at very high shear rates. However, these studies did not focus on the temperature dependence of the rheology of digested sludge, which would fundamentally affect the flow properties and consequent operating conditions of the digester.…”
Section: Introductionmentioning
confidence: 99%